High-Level Extracellular Expression of a New β-N-Acetylglucosaminidase in Escherichia coli for Producing GlcNAc - Li, Congna; Jiang, Shun; Du, Chao; Lu, Zhenghui; He, Nisha; Zhou, Yuling; Jiang S, Sijing; Zhang G, Guimin (Frontiers in Microbiology, 2021)
Abstract N-acetyl-β-D glucosamine (GlcNAc) is wildly used in the cosmetics, nutraceutical and pharmaceutical. The traditional chemical process for GlcNAc production from chitin cause serious acidic pollution. Therefore, the enzymatic hydrolysis become a great promising and alternate strategy to produce GlcNAc. β-N-acetylglucosaminidase (NAGase) can hydrolyze chitin to produce GlcNAc. Here, a GH3 family NAGase encoding gene BlNagZ from Bacillus licheniformis was expressed extracellularly in Escherichia coli guided by signal peptide PelB. The recombinant BlNagZ presented the best activity at 60 ºC and pH 5.5 with a high specific activity of 13.05 U/mg. The BlNagZ activity in the fermentation supernatant can reach 13.5 U/mL after optimizing the culture conditions, which is 4.2 times higher than optimization before. Finally, combining BlNagZ with chitinase ChiA we identified before, the efficiency of chitin conversion to GlcNAc can reach 89.2% within 3.5 hours. In all, this study provided not only a high active NAGase, but also a secreted expression strategy to reduce the cost of production, which is conducive to the industrial application.